Hegemonic childhood in the Polish community of West Prussia in the second half of the 19th and early 20th centuries - Paweł Śpica (Problemy Wczesnej Edukacji)
In this article, I present the hegemonic concept of childhood in the second half of the 19th and early 20th centuries among the Polish community of West Prussia. The subject of the analyses was the content of articles dealing with children’s issues, published in the local Polish press. The essential feature of the hegemonic discourse of childhood for the Polish community in the analysed region was that it was clearly based on the Catholic religion and national ideas, as well as on a strong relationship with the conservative and post-feudal image of family relations. The conducted research made possible the identification of seven basic categories of the hegemonic understanding of childhood in the Polish environment of West Prussia, which are: Polish and Catholic childhood, childhood sensitive to the needs of others, heroic childhood, tidy and pupil childhood, neat and orderly childhood, childhood based on obedience and subordination, sexual purity childhood.